SOSIALISASI INTELLIGENT RESEARCH AND INNOVATION SERVICES (IRIS) 1103 BAGI CIVITAS AKADEMIKA UNS (Studi Evaluasi Model CIPP terhadap Sosialisasi IRIS1103 oleh Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Sebelas Maret) - Suranti, Sri (Interaksi: Jurnal Ilmu Komunikasi, 2016)
Abstract: The objectives of this research to evaluate the success of socialization activities IRIS1103 organized by LPPM UNS for civitas akademika UNS based on CIPP evaluation model, supported quantitative and qualitative data. Quantitative data are collected using questionnaires given to educators in the environment UNS. While qualitative data obtained through interviews with researchers and implementers of the target IRIS1103 and socialization study documents used in the activities of socialization.Based on the results of the CIPP evaluation model (Context, Input, Process, Product) on the communication element (Communicator, message, and partisipant) in the IRIS1103 socialization activities be declared successful and effective way to improve understanding and knowledge of civitas akademika UNS about Groove Research and community services (P2M) IRIS1103 in the application which ultimately encourage them to create new routines, visit iris1103.uns.ac.id every page requires information on the P2M.Â Key words: socialization, CIPP evaluation model, IRIS1103, research and community services